FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA MELALUI PENERAPAN SISTEM KEUANGAN DESA (SISKEUDES): Studi Pada Desa Di Kecamatan Pemayung - Sulis Septiani; Wirmie Eka Putra; Fitrini Mansur (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2025)
This study aims to determine the factors that affect the accountability of village fund management through the application of the Village Financial System (Siskeudes) as an intervening variable. The population in this study were all village officials in the Pemayung District area totaling 18 villages with the criteria for respondents, namely the Village Head, Village Secretary, Head of Financial Affairs (Village Treasurer), and Chairman or Member of BPD. The research sample was selected using saturated sampling with a sample size of 72 respondents. This research method uses quantitative techniques. This study uses primary data obtained by distributing questionnaires to respondents. This research data analysis technique uses PLS-SEM with SmartPLS software. The results showed that the role of village officials and community participation had no effect on the accountability of village fund management while the competence of village officials and the application of Siskeudes had a positive effect on the accountability of village fund management. The role of village officials has a positive effect on the application of Siskeudes. The competence of village officials has a negative effect on the application of Siskeudes. Community participation has no effect on the application of Siskuedes. The role of village officials and the competence of village officials affect the accountability of village fund management through the application of Siskeudes. Community participation has no effect on the accountability of village fund management through Siskeudes.